Decabromodiphenyl ether induces male reproductive toxicity by activating mitochondrial apoptotic pathway through glycolipid metabolism dysbiosis. (December 2021) - Zhang, Yue; Li, Xiangyang; Jing, Li; Zhou, Guiqing; Sang, Yujian; Gao, Leqiang; Jiang, Shuqin; Shi, Zhixiong; Ge, Wei; Sun, Zhiwei; Zhou, Xianqing
Abstract: Decabromodiphenyl ether (BDE-209), an extensively used flame retardant, exists widely in the environment. Although male reproductive toxicity induced by BDE-209 has been reported, its mechanisms remain unclear. To explore the role of glycolipid metabolism in male reproductive toxicity and the potential mechanisms, forty male SD rats were divided into four groups and given gavage with BDE-209 at 0, 5, 50, and 500 mg/kg/d for 28 days. In vitro, the spermatogenic cell lines GC-2spd cells were divided into four groups: the control group, 32 μg/mL BDE-209 group, 32 μg/mL BDE-209 + 0.4 μM Fatostatin (the inhibitor of SREBP-1) group, and 0.4 μM Fatostatin group. Our results showed that BDE-209 decreased sperm quality and quantity, which was correlated with glycolipid metabolism dysbiosis of testis. The levels of glucose, triglyceride, and total cholesterol were negatively correlated with sperm concentration, and triglyceride and total cholesterol levels were negatively correlated with sperm motility, while positively correlated with the sperm malformation rate. Moreover, BDE-209 exposure activated the glycolipid metabolism pathways (PPARγ/RXRα/SCAP/SREBP-1) and mitochondrial apoptotic pathway, thereby inducing the apoptosis of spermatogenic cells. In vitro, BDE-209 caused triglyceride and total cholesterol disorder and apoptosis of GC-2spd cells, the lipid metabolism pathways inhibitor fatostain downregulated the elevation of triglyceride and total cholesterol concentrations, and suppressed apoptosis and the activation of the mitochondrial apoptotic pathway in GC-2spd cells caused by BDE-209. Our results indicated that BDE-209 induced male reproductive toxicity by causing glycolipid metabolism dysbiosis of testis resulting in activating of the mitochondrial apoptotic pathway in spermatogenic cells. The study provides new insight into the mechanisms of male reproductive toxicity caused by BDE-209. Graphical abstract: Image 1 Highlights: Testicular glucose and lipid levels were correlated with sperm quality and quantity. BDE-209 caused testicular lipid metabolic disorder via SCAP/SREBP-1 pathway. Glycolipid metabolism involved in BDE-209-induced mitochondrial apoptotic pathway. BDE-209 caused sperm abnormality via cell apoptosis through lipid disorders.